Genetic basis of the interaction between Stenotrophomonas maltophilia and Caenorhabditis elegans from both host and pathogen perspectives - Radeke, Leah Jean (Kansas State University, 2018)
Stenotrophomonas maltophilia is an opportunistic bacterial pathogen found ubiquitously in the environment. Although S. maltophilia is an emerging pathogen associated with hospital-acquired infections in patients with respiratory diseases, particularly cystic fibrosis, very little is known about its mechanism of pathogenesis in any system. In addition, S. maltophilia isolates vary in pathogenicity to several hosts and are genetically diverse, including variation in virulence factors. In this thesis, I address the genetic basis of S. maltophilia pathogenesis from both host and bacterial perspectives. Our lab has previously developed Caenorhabditis elegans as a model for S. maltophilia infection. Stenotrophomonas is found in relatively high abundance in the microbiome of C. elegans, making it a suitable platform for studying S. maltophilia-host interactions. I performed a transcriptomic analysis to determine C. elegans responses to several S. maltophilia strains of varying pathogenicity. Treatments included K279a, an avirulent clinical isolate, JCMS, a virulent environmental strain isolated in association with nematodes near Manhattan, KS, and JV3, an even more virulent environmental isolate. Overall, I found that most genes (89%) that are differentially expressed in response to pathogenic S. maltophilia strains are upregulated, with many even further upregulated in response to the more virulent strain, JV3. Using information from a variety of transcriptomic datasets, I found that most of these genes are also commonly differentially expressed in C. elegans in response to other pathogens. Many more genes were differentially expressed specifically in response to JV3 when compared to all other strains (221 genes) than JCMS as compared to all other strains (14 genes), suggesting JV3 has unique virulence mechanisms that could explain its observed increased virulence. Candidate genes were chosen from the above differentially expressed gene sets (differentially expressed in response to both pathogenic S. maltophilia strains or in a strain-specific manner) for functional analysis. Mutational analysis of these candidate genes revealed that several mutants caused increased susceptibility of C. elegans to pathogenic S. maltophilia, regardless of the strain(s) that caused differential expression of that gene. Furthermore, many of these mutants also caused increased susceptibility to K279a, suggesting that K279a may also employ virulence mechanisms that wild-type C. elegans are able to defend against. To address the pathogen side of the interaction, we analyzed draft assemblies of the S. maltophilia strains, with the addition of another slightly pathogenic environmental strain, R551-3. We hypothesized that differences in observed pathogenicity and host responses to strains of S. maltophilia could be explained by differences in their genomes. When comparing draft assemblies to their respective reference genomes, few differences were observed. However, several genomic features were present in some strains and absent in others, including components of the CmeABC efflux pump and the Type IV secretion system, that might play a role in different virulence mechanisms. Genome-wide comparison of shared and unique genetic features across many S. maltophilia strains revealed that most S. maltophilia genes are strain-specific, suggesting that many potential virulence factors are unique and have yet to be functionally analyzed. Overall, variation in observed pathogenicity, differences in host transcriptional responses, and comparative genomics of S. maltophilia strains reveal that strain-specific mechanisms play important roles in S. maltophilia pathogenesis.
Keywords: Biology; Genetics; Caenorhabditis elegans; Stenotrophomonas maltophilia; Nematode-bacterial interactions